Variables asociadas al fenómeno del ciberbullying en adolescentes colombianos - Pacheco, Jesús Redondo (2022)
This research describes the associated variables that participate in the phenomenon of cyberbullying in 1080 Colombian adolescents with an age range of 10 to 19 years (M = 13.48; SD = 1.75), using the Victimization Scale through cell phone and internet and the Cyber-Attack Scale (adapted by Buelga, Cava, & Musitu in 2010). The results show that age, time of internet use and internet availability are risk factors associated with being cyber-victim through the internet, and the age, female sex and time of having a cell phone, in the case of Cybervictimization through this device. Regarding cyber-aggression, the risk factors found were female sex, cell phone and internet access, and if that internet is used at home, in addition to internet browsing time and its use. These results will help to know in greater depth the phenomenon, allowing to propose effective intervention programs before its diverse forms that evolve and change in a vertiginous way.